Misdemeanor courts, due process, and case outcomes - Smith, Alisa (Criminal justice policy review, 2020)
Very little research on courts and sentencing outcomes focuses on misdemeanor courts despite the fact that most crime processed through the criminal justice system is misdemeanor in nature. In fact, the overwhelming empiricism in this area is on felony court outcomes at either the federal or state levels. This research utilized a mixed methodology approach, a combination of observation, survey, and secondary data, to explore misdemeanor court outcomes across the State of Florida. In particular, this research focused on the extent of due process afforded misdemeanor defendants and how this impacted case outcomes. Findings indicate an overall lack of due process and awareness of due process rights across the vast majority of cases. This study also explored sentencing outcomes via traditional metrics associated with contemporary sentencing research. Findings suggest that misdemeanor courts processing operate much differently than felony courts. The implications for future research and policy are discussed.